The Glutamate-gated Chloride Channel Facilitates Sleep by Enhancing the Excitability of Two Pairs of Neurons in the Ventral Nerve Cord of Drosophila. - Fan, Y.; Tian, Y.; Han, J. (Neuroscience bulletin, 2025)
Sleep, an essential and evolutionarily conserved behavior, is regulated by numerous neurotransmitter systems. In mammals, glutamate serves as the wake-promoting signaling agent, whereas in Drosophila, it functions as the sleep-promoting signal. However, the precise molecular and cellular mechanisms through which glutamate promotes sleep remain elusive. Our study reveals that disruption of glutamate signaling significantly diminishes nocturnal sleep, and a neural cell-specific knockdown of the glutamate-gated chloride channel (GluCl?) markedly reduces nocturnal sleep. We identified two pairs of neurons in the ventral nerve cord (VNC) that receive glutamate signaling input, and the GluCl? derived from these neurons is crucial for sleep promotion. Furthermore, we demonstrated that GluCl? mediates the glutamate-gated inhibitory input to these VNC neurons, thereby promoting sleep. Our findings elucidate that GluCl? enhances nocturnal sleep by mediating the glutamate-gated inhibitory input to two pairs of VNC neurons, providing insights into the mechanism of sleep promotion in Drosophila.